The Influence of the Shafie School on Fatwa Methodologies in Malaysia: Toward the Unity of Ummah’s Objective - Harun, Muhammad Safwan; Ali, Abdul Karim; Ahmad Syahir, Aminun Nabil (Mazahib, 2024)
Maqāṣid al-shariah, which refers to the aim or goal intended by Islamic law to benefit humankind, is closely related to the issuance of fatwas. This condition raises the question of whether maqāṣid al-shariah is fully considered in the fatwa issuance process in Malaysia. The methodology used in issuing fatwas in Malaysia is unique as the Shafie school is the primary reference, and the methodology aims to create a systematic fatwa management system in preserving unity. However, the approach does not generally embrace maqāṣid al-shariah, such as freedom, and favors an easier option (al-taysīr) to examine diverse views outside the Shafie school. This condition raises questions about the capability of the sectarian methodology practiced in the current issuance of fatwas and whether the fatwa methodology tied to the Shafie school can manifest maqāṣid al-shariah in every law. This paper aims to examine the achievement of maqāṣid al-shariah in the fatwa methodology that contains the strong tradition and influence of the Shafie school. Through inductive, deductive, and comparative document research, this study revealed three main findings. First, maqāṣid al-shariah in the fatwa methodology in Malaysia is applied through shariah arguments parallel with the uṣul al-fiqh framework. Second, the Malaysian fatwa methodology that references the final view of the Shafie school is intended to achieve uniformity and unity among the Muslim-majority community in Malaysia, which coincides with maqṣad wihdatul ummah. Third, when maṣlahah is not achieved in certain circumstances, views of schools other than the Shafie school can be consulted.